Effect of warm multidirectional forging on the microstructure and mechanical properties of a high-nitrogen austenitic steel - Kim, Anna V.; Akkuzin, Sergey A.; Litovchenko, Igor Yu; Polekhina, Nadezhda A.; Kushnereva, D. S. (Russian physics journal)
The features of the microstructure of the high-nitrogen austenitic VNS-53-Sh steel after multidirectional isothermal forging have been studied by transmission electron microscopy. The formation of an inhomogeneous deformed microstructure is shown. Regions of significant fragmentation are observed, in which the grain-subgrain structure is refined. Areas with plastic deformation localized in shear bands are found. As a result of multidirectional forging, the strength properties of steel increase compared to the initial state. The yield strength at T = 20°C increases by a factor of 2.5, with elongation decreasing down to ≈10%. At the elevated test temperature (275°C), the yield strength increases by a factor of 4.5, and the elongation decreases to ≈6%. Relying on the structural studies, this is attributed to substructural and dislocation strengthening.